Operationalizing the C's of Teamwork in an Intelligent Tutoring System. (September 2017) - Bonner, Desmond; Ouverson, Kaitlyn; Gilbert, Stephen; Dorneich, Michael; Winer, Eliot; Sinatra, Anne; Macallister, Anastacia; Kohl, Adam
One of the difficulties in creating a team-focused intelligent tutoring system (ITS) is defining the measures used to assess the team's performance. While the team research literature offers nine C's of teamwork to consider, e.g., cooperation, communication, etc., it can also be difficult to implement these in real-world practice. This paper reviews the approach used in three team ITSs in which the C's were used, offering guidance for future implementation of team tutors.